4+3n=5(2-2n)

Simple and best practice solution for 4+3n=5(2-2n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+3n=5(2-2n) equation:


Simplifying
4 + 3n = 5(2 + -2n)
4 + 3n = (2 * 5 + -2n * 5)
4 + 3n = (10 + -10n)

Solving
4 + 3n = 10 + -10n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '10n' to each side of the equation.
4 + 3n + 10n = 10 + -10n + 10n

Combine like terms: 3n + 10n = 13n
4 + 13n = 10 + -10n + 10n

Combine like terms: -10n + 10n = 0
4 + 13n = 10 + 0
4 + 13n = 10

Add '-4' to each side of the equation.
4 + -4 + 13n = 10 + -4

Combine like terms: 4 + -4 = 0
0 + 13n = 10 + -4
13n = 10 + -4

Combine like terms: 10 + -4 = 6
13n = 6

Divide each side by '13'.
n = 0.4615384615

Simplifying
n = 0.4615384615

See similar equations:

| 16=s-50 | | 29=q-51 | | 3a+5b=15 | | 8k+5k-10k= | | 56-d=27 | | 2+2u+7=42 | | w-10=58 | | 6=k-15 | | 4=m-63 | | 7x-3=x+7 | | 12-(3x-6)-5(7-x)= | | 39-w=2 | | y-65=9 | | (4t+9)-(-2+7)=0 | | A=p+pnr | | p-10=25 | | 8=n-65 | | 52q=32 | | b^4-ab^3+b^2c=0 | | 7*cos^2*x-cos*x-8=0 | | 71=-9n+8 | | 3*cos*2*x-5*cos*x-1=0 | | -3(y-2)=-5y+18 | | 7w-9=5(w+1) | | 7(y+6)-2y=2 | | 22-2x=14 | | .5x-2.4=.6 | | -4v+8(v-2)=-4 | | -3(4t-3)+5t=6t-5 | | 48+x(9+3)=288 | | 7u+5=5 | | -4v+8(v+2)=-4 |

Equations solver categories